Return on Equity pada Bank Syariah: Dampak Pembiayaan Murabahah, Mudharabah, Musyarakah, Ijarah dan Qard - Nofa Maulidiyah; Susmita Dian Indiraswari; Irma Tyasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of murabahah, mudharabah, musyarakah, ijarah, and qard financing on Return On Equity (ROE). The secondary data used was obtained from the quarterly financial statements of Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the period 2022-2024. The purposive sampling method was used for sample selection, and data analysis was carried out with SPSS software, which included descriptive analysis, multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that murabahah, mudharabah, musyarakah, ijarah, and qard financing simultaneously affect Return On Equity. Partially, murabahah, mudharabah, and ijarah financing affect Return On Equity, while musyarakah and qard financing have no effect on Return On Equity.